Faktor-Faktor Penyebab Depresi Pasca Persalinan - Cici Mulyani; Ayu Dekawaty; Suzanna Suzanna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the factors that cause postpartum depression. This research method is a systematic review by searching for article data sources through electronic databases, namely Pubmed, ScienceDirect, Proquest, and Google Scholar (2016-2020). The results showed that 18 research articles included higher factors for postpartum depression, namely young age, multiparity parity, history of abortion, and lack of husband and family social support. Mothers who work high experience postpartum depression. The factors that are more likely to experience postpartum depression are a history of childbirth complications, the sex of the unwanted baby, higher education, widowed or unmarried women, unplanned pregnancy, low economy, domestic violence, and marital satisfaction. In conclusion, the factors that can cause postpartum depression are age, parity, history of abortion, social support, husband, family, occupation, history of childbirth complications, sex of the baby, education, marital status, unplanned pregnancy, and economic status, violence. Household and marital satisfaction. Keywords: Causing Factors, Depression, Postpartum